Counseling individuals through the lifespan - Wong, Daniel W.; Hall, Kimberly R.; Wong Hernandez, Lucy (Thousand Oaks Sage, 2021)
"Organized around the 2016 CACREP Standards, Counseling Individuals Through the Lifespan introduces readers to the fundamentals of the counseling process during each stage of human development. Topics such as the client-counselor relationship, counseling theory, research, and interventions are addressed with a focus on caring for the total person within his/her environment and culture. Emphasizing the importance of intentionality and self-reflection, the chapters include case illustrations and guided practice exercises to further the development of successful 21st century counselors. The Second Edition has been revised to include cutting-edge research on counseling practice and timely topics including bullying and acts of violence in schools"--
Includes bibliographical references and index.
Keywords: Counseling; Developmental psychology